2015
DOI: 10.1242/jcs.169441
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide RNAi screen for nuclear actin reveals a network of cofilin regulators

Abstract: Nuclear actin plays an important role in many processes that regulate gene expression. Cytoplasmic actin dynamics are tightly controlled by numerous actin-binding proteins, but regulation of nuclear actin has remained unclear. Here, we performed a genome-wide RNA interference (RNAi) screen in Drosophila cells to identify proteins that influence either nuclear polymerization or import of actin. We validate 19 factors as specific hits, and show that Chinmo (known as Bach2 in mammals), SNF4Aγ (Prkag1 in mammals) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 56 publications
(87 reference statements)
1
23
0
Order By: Relevance
“…Nuclear actin filaments are most likely formed by mechanisms similar to those in the cytoplasm (Kokai et al 2014), but the regulation of polymerization is supposedly different in the two cellular compartments because the factors required for microfilament network formation are not constantly present in the nucleus; they shuttle continuously between the cytoplasm and the nucleus (Kumeta et al 2012). Moreover, new regulators of actin polymerization have been identified recently in a genome-wide screen in Drosophila S2R+ cell nuclei among which the depletion of Nucleoporin 98, Capt or Lam proteins inhibited the formation of actin rods in the nucleus (Dopie et al 2015). To date, F-actin structures have only been detected in the nucleus with antibodies that recognize unique actin conformations (Schoenenberger et al 2005) and under specific conditions such as DMSO treatment (Fukui and Katsumaru 1980), heat shock (Nishida et al 1987), ATP depletion (Pendleton et al 2003), nucleus transplantation (Miyamoto et al 2011), serum induction (Grosse and Vartiainen 2013), activation of the formin mDia in the nucleus (Baarlink et al 2013), forced overexpression of nuclear actin (Kalendova et al 2014;Kokai et al 2014), cell spreading (Plessner et al 2015), viral infection (Feierbach et al 2006;, or certain diseases (Bamburg et al 2010;Munsie et al 2011).…”
Section: Nuclear Actinmentioning
confidence: 99%
“…Nuclear actin filaments are most likely formed by mechanisms similar to those in the cytoplasm (Kokai et al 2014), but the regulation of polymerization is supposedly different in the two cellular compartments because the factors required for microfilament network formation are not constantly present in the nucleus; they shuttle continuously between the cytoplasm and the nucleus (Kumeta et al 2012). Moreover, new regulators of actin polymerization have been identified recently in a genome-wide screen in Drosophila S2R+ cell nuclei among which the depletion of Nucleoporin 98, Capt or Lam proteins inhibited the formation of actin rods in the nucleus (Dopie et al 2015). To date, F-actin structures have only been detected in the nucleus with antibodies that recognize unique actin conformations (Schoenenberger et al 2005) and under specific conditions such as DMSO treatment (Fukui and Katsumaru 1980), heat shock (Nishida et al 1987), ATP depletion (Pendleton et al 2003), nucleus transplantation (Miyamoto et al 2011), serum induction (Grosse and Vartiainen 2013), activation of the formin mDia in the nucleus (Baarlink et al 2013), forced overexpression of nuclear actin (Kalendova et al 2014;Kokai et al 2014), cell spreading (Plessner et al 2015), viral infection (Feierbach et al 2006;, or certain diseases (Bamburg et al 2010;Munsie et al 2011).…”
Section: Nuclear Actinmentioning
confidence: 99%
“…In specific settings, like the giant quiescent nuclei of amphibian oocytes, a filamentous actin network has scaffolding functions and links nuclear pore complexes to the nuclear interior (Clark & Rosenbaum, 1979;Gounon & Karsenti, 1981;Kiseleva et al, 2004;Feric & Brangwynne, 2013). In somatic cells, sub-populations of nuclear actin have distinct mobilities, suggesting existence of polymeric forms (McDonald et al, 2006;Dopie et al, 2012), and several regulators of actin polymerisation have been found in nuclei (Wu et al, 2006;Yoo et al, 2007;Khoudoli et al, 2008;Obrdlik & Percipalle, 2011;Miyamoto et al, 2013;Dopie et al, 2015). However, dynamic nuclear actin polymerisation has only been described upon serum stimulation of mouse fibroblasts (Baarlink et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear actin filaments have also been noted following treatment with actin-depolymerizing drugs (Belin et al, 2013;Sen et al, 2015;Yahara et al, 1982) and upon dysregulation of actin-binding proteins such as exportin-6 (Dopie et al, 2015(Dopie et al, , 2012 and MICAL-2 (Lundquist et al, 2014). Furthermore, acute cellular stress, such as heat shock, as well as huntingtin mutations, lead to the formation of micron long actin and cofilin nuclear rods (Munsie et al, 2011;Nishida et al, 1987).…”
Section: Introductionmentioning
confidence: 99%